Study on economy of flue gas ultra-low emission in coal-fired power. (October 2019) - Zhang, Yang; Liu, Qingsong; Wei, Hongge; Du, Zhen; Zhu, Yue
Abstract: Along with the rapid progress of flue gas ultra-low emission reconstruction in coal-fired power plants in recent years, flue gas pollutant control is markedly improved, but the economic efficiency of flue gas ultra-low emission was undervalued. Given the present situation of flue gas ultra-low emission in coal-fired power plants, several typical problems about economic efficiency have been analyzed and discussed, including coordinated optimization operation, emissions target control, energy efficiency management on the basis of extensive and thorough investigations. Relevant guidance and countermeasures are proposed to provide further reference for subsequent operation and maintenance of power generation enterprises.